Lean body mass as a predictor of performance of young Iranian elite weightlifters - Siahkouhian, M.; Azimi, F.; Hedayatnejad, M. (South African Journal for Research in Sport, Physical Education and Recreation, 2016)
The aim of this study was to evaluate the relationships of body composition and anthropometric variables with the performance of young Iranian elite weightlifters. Forty-two subjects (age 16.21±3.22 years) volunteered to participate in the study. All subjects competed at the Iranian National Championship. Body composition and anthropometric variables including lean body mass (LBM), body mass index (BMI), percentage body fat (%BF), height, shoulder circumference, chest circumference, waist to hip ratio (WHR), as well as the performance of the weightlifters (snatch; clean & jerk; front squat; back squat), were measured. The results showed a strong correlation between LBM and the performance of the weightlifters (p=0.001). Moderate correlations between the remaining body composition variables and the performance of the weightlifters were obtained. However, low negative correlations were found between the performance of the weightlifters and the %BF and WHR values. It can be concluded that there was a relationship between LBM and weightlifting performance. However, weak negative relationships existed among %BF and WHR with the performance of weightlifters. Therefore, LBM was the major determinant in weightlifting, while %BF played a very small role in the determination of weightlifting performance.